2022
DOI: 10.1038/s41420-022-01095-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic TRIB2 interacts with and regulates PKM2 to promote aerobic glycolysis and lung cancer cell procession

Abstract: PKM2 is an important regulator of the aerobic glycolysis that plays a vital role in cancer cell metabolic reprogramming. In general, Trib2 is considered as a “pseudokinase”, contributing to different kinds of cancer. However, the detailed roles of TRIB2 in regulating cancer metabolism by PKM2 remain unclear. This study demonstrated that TRIB2, not a “pseudokinase”, has the kinase activity to directly phosphorylate PKM2 at serine 37 in cancer cells. The elevated pSer37-PKM2 would subsequently promote the PKM2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Furthermore, we found knockdown of TRIB2 to significantly inhibit PDGF‐BB‐induced VSMC proliferation, indicating that PDGF‐BB‐induced TRIB2 expression positively regulates VSMC proliferation. Our findings are consistent with previous reports that TRIB2 knockdown impairs the growth ability of various cancer cells, including HepG2 cells and HCT116 cells (a human colon cancer cell line) (Liu et al, 2022). However, another study did not detect any significant effects of TRIB2 silencing on the proliferation of HL7702 hepatocytes (Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, we found knockdown of TRIB2 to significantly inhibit PDGF‐BB‐induced VSMC proliferation, indicating that PDGF‐BB‐induced TRIB2 expression positively regulates VSMC proliferation. Our findings are consistent with previous reports that TRIB2 knockdown impairs the growth ability of various cancer cells, including HepG2 cells and HCT116 cells (a human colon cancer cell line) (Liu et al, 2022). However, another study did not detect any significant effects of TRIB2 silencing on the proliferation of HL7702 hepatocytes (Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…Thus, increased TRIB2 expression may significantly affect VSMC proliferation and influence neointima formation. Our data supports previous studies that have reported TRIB2 overexpression in the proliferative stage of cancers such as lung and liver cancer (Liu et al, 2022). Accordingly, TRIB2 may play an important role in the initiation of cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…Glucose carbons are essential for biomass synthesis through the glycolysis and the pentose phosphate pathways, with lactic acid and nucleic acid precursors produced as major end products ( 14 , 70 , 71 ). The pyruvate kinase M2 (PKM2) isoform, which is abundantly expressed in most malignant cancers, produces pyruvate-derived lactic acid with minimal ATP synthesis ( 14 , 72 75 ). In other words, most of the glucose-derived lactic acid coming from the tumor cells is produced with little ATP synthesis through glycolysis.…”
Section: Fermentation Metabolites Acidify the Gbm Microenvironmentmentioning
confidence: 99%
“…The glutaminolysis pathway (red) becomes dominant in tumor cells with inefficient OxPhos and that express the dimeric PKM2 isoform. PKM2 is expressed in GBM and produces less ATP through glycolysis than does the PKM1 isoform ( 73 , 75 , 195 , 196 ). The elevation of ketone bodies (D-β-hydroxybutyrate and acetoacetate) through KD will indirectly reduce ATP synthesis through the succinate CoA ligase (SUCL) reaction by diverting CoA from succinate to acetoacetate.…”
Section: The Simultaneous Restriction Of Glutamine and Glucose Will R...mentioning
confidence: 99%
“…These findings are consistent with previous studies showing that PKM2 isoform is expressed in various human glioma cell lines (Luan et al, 2015). Unlike the PKM1 isoform, which produces ATP in the glycolytic pathway, the dimerized PKM2 isoform exists as a low-affinity enzyme which diverts phosphoenolpyruvate toward auxiliary pathways that result in lactate production while circumventing the net ATP step in glycolysis (Liu and Vander Heiden, 2015; Chinopoulos, 2020; Seyfried et al, 2020; Liu et al, 2022). Hence, caution is necessary in considering lactate as a quantitative biomarker for ATP content through glycolysis in glioma cells that express the PKM2 isoform.…”
Section: Discussionmentioning
confidence: 99%